Considerations about traumatic diaphragmatic hernia in small animals - Raíne da Luz de Toledo; Sheila Canevese Rahal; Luciane dos Reis Mesquita; Maria Jaqueline Mamprim; Geovane José Pereira; Cláudia Valéria Seullner Brandão; Jeana Pereira da Silva; Ricardo Shoiti Ichikawa (Medicina Veterinária, 2024)
Diaphragmatic hernia is a relatively common disorder in routine surgical procedures for small animals. This hernia is characterized by discontinuity of the diaphragm due to a rupture or defect, which may result in the displacement of abdominal organs into the thoracic cavity. Therefore, this review aims to provide information about the anatomy of the diaphragm and associated structures, as well as the causes, clinical signs, diagnosis, and treatment options for acquired diaphragmatic hernia. The diaphragm is an inspiratory muscle composed of a muscle portion that surrounds a central tendon. Traumatic diaphragmatic hernia is commonly associated with motor vehicle accidents. The diagnosis is based on clinical history and physical examination, but the final definition requires imaging studies, in which plain radiographic examination is the most frequently used. However, an ultrasound examination is necessary in some cases. Treatment involves surgical correction of the rupture, usually performed through a median celiotomy.